Analysis of Internet Use in Undergraduate Colleges of Mangalore - Sujatha, H.R. (DESIDOC Journal of Library & Information Technology, 2010)
The advent of Internet and its resources have revolutionised the academic world. A significant transition can be seen in the academic communities approach and the way they seek information, and the methods they employ for teaching and learning activities. This paper is based on a research project, funded by the University Grants Commission, to analyse the patterns of use of Internet among the teachers and the students of the first grade colleges in Mangalore city. The study also investigated the level of academic community’s access to the Internet, reasons for non-use of Internet, satisfaction with the Internet facilities provided in these institutions as well as the problems faced in the use of Internet. A well structured questionnaire was distributed among the 390 teachers and students of the five colleges in the Mangalore city. Out of which 335 questionnaires were received back duly filled in. The response rate was 85.9 per cent. The study revealed that the level of student’s access to the Internet was low and the major reason was that at the time of the study, computers with Internet facilities were inadequate. The findings also revealed that the rate of Internet use was more among the teachers and students of Commerce and Science faculty as compared to the faculty of Arts. However, majority of the students expressed their interest in the use of Internet and its resources and were enthusiastic in improving their skills in the use of the Internet. The study recommends the provision of more computers with Internet facilities, better access speed, and providing more orientation/training programmes in the use of Internet in these institutions. http://dx.doi.org/10.14429/djlit.31.1.761